2014
DOI: 10.5758/vsi.2014.30.2.56
|View full text |Cite
|
Sign up to set email alerts
|

The Laterality of Deep Vein Thrombosis in the Pelvic and Lower Extremity Veins

Abstract: Purpose:This study aimed to determine whether deep vein thrombosis (DVT) predominantly occurred on a particular side in the pelvic and lower extremity veins.Materials and Methods:Among 259 consecutive patients with leg swelling, 65 were confirmed to have DVT in the pelvis and lower extremities, and enrolled in this study. The serum levels of initial D-dimer, antithrombin III, tissue plasminogen activator, factor VIII, proteins C and S, anticardiolipin antibodies immunoglobulin (Ig) G and IgM and lupus anticoag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Older trauma patients are at a significantly higher risk for thromboembolic events compared to younger patients. 28,29 Furthermore, the peak of DVT incidence has been reported at ages between 45 and 59 years, an age group that was much more frequent in our study cohort compared to the CRASH-2 cohort. 30 In recent studies, it was demonstrated that in hospitalized older patients with traumatic brain injury (TBI) and in patients with greater TBI severity, incidence of acute thromboembolic events was significantly higher.…”
Section: Discussionmentioning
confidence: 50%
“…Older trauma patients are at a significantly higher risk for thromboembolic events compared to younger patients. 28,29 Furthermore, the peak of DVT incidence has been reported at ages between 45 and 59 years, an age group that was much more frequent in our study cohort compared to the CRASH-2 cohort. 30 In recent studies, it was demonstrated that in hospitalized older patients with traumatic brain injury (TBI) and in patients with greater TBI severity, incidence of acute thromboembolic events was significantly higher.…”
Section: Discussionmentioning
confidence: 50%
“…Shin's study mentioned above found 57% left-sided predominance of DVT, but the finding seemed to be restricted to females who had left-predominant DVT in 74.2%. 6 The casecontrol study by Narayan et al found that female sex had odds ratio 6.41 for compression of the left iliac vein, providing an underlying cause for the observed laterality associated with female sex. 7 It has been proposed that the accentuated lordosis of the lower spine in females pushes the left iliac vein forward against the right iliac artery (briefly reviewed by Harbin et al) 24 We did not perform adjustment for multiple comparisons because all analyses were driven by specific hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis by sex was also performed as we were aware that left-side predominance in DVT is prominent in females. 6 Sex data were missing in 70 cases, leaving 68,435 cases for this subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…May–Thurner syndrome is three-to-eight times more frequent on the left side than on the right [ 4 , 5 ] and accounts for approximately 50%-60% of the cases of left IF DVT [ 6 , 7 ]. This condition is considered as one of the main contributors to the left-sided predominance of DVT in the lower extremity [ 8 - 10 ]; thus, correction of the mechanical compression is often necessary for patients with left-sided DVT to reduce the risk of recurrent DVT and PTS [ 11 ]. CDT is indicated only for extensive proximal DVT because of the increased risk of major bleeding events [ 12 ].…”
Section: Introductionmentioning
confidence: 99%